Harmonizing the Tenth Malaysia Plan priorities with the new economic model and the green world order - Mustafa, Saleem; Saad, Shahbudin (2011)
The New Economic Model (NEM) integrates innovative ideas in socio‐economic development of Malaysia. Specifically, it aims at achieving high income, sustainability and inclusiveness in the economic transformation through this new policy initiative. NEM will build resilience into the economic system for sustainable benefits to the society. The sustainability dimension of NEM will require focus on natural resources. This is achievable by aligning our activities with the new concept of ‘Green World Order’. Under this concept, there is a need for making changes in our activities. Development planning will require resetting in the light of environmental limitations to achieve the goals of NEM. With the valuation of ecosystem services becoming increasingly important, we should pursue this matter with a sense of urgency for positioning Malaysia as a major player in the global environmental governance and claimant to a substantial stake in the fund to mitigate the effects of climate change. Out of US$33 trillion per year as the economic value of world ecosystems, our resources such as forests, mangroves and seagrasses, wetlands and groundwater recharge systems, coral refs and ability to implement green technology projects should enable the country to have a significant stake and role in global environmental mitigation programs. With an effective action plan, Malaysia can take advantage of the growing carbon market and green economy. Investment in carbon sinks should be a sort of foreign direct investment free of strings and riders while supporting our national goals of food security, environmental conservation, education, health care and socio‐economic development. However, we need to develop expertise to deal with international institutions in carbon economy. We propose setting up an autonomous center to address all such matters related to human resource needs and global environmental governance to position Malaysia for a fair share of benefits that will accrue.